Modeling the effects of eruptive and seismic activities on flank instability at Mount Etna, Italy. Issue 10 (24th October 2013) - Bozzano, F.; Gaeta, M.; Lenti, L.; Martino, S.; Paciello, A.; Palladino, D. M.; Sottili, G.
Abstract [1] The identification and evaluation of trigger mechanisms for volcano flank instabilities and/or collapse represent a key issue for risk assessment in densely populated volcanic areas, as well as in long‐distance settings, particularly in case of island or coastal volcanoes. Here we address quantitatively the effects of external (seismic) and inner (magmatic) forcing on the stress‐strain state associated to flank instabilities at Mount Etna (Sicily, southern Italy) by means of a 2‐D finite difference method numerical modeling. Modeled seismic actions include strong near‐field, strong far‐field, and low‐magnitude near‐field earthquakes. Magmatic actions consider the inner pressure changes induced by energetic lava fountains in the summit crater area and subvertical and oblique dike ascent below the summit area. Model results are validated in light of available monitoring data and recent eruptive activity. Numerical results show that the main strain effects are produced by high‐magnitude near‐field earthquakes (expected return time of 103 yrs) and by vertical uprise of a magma dike below the volcano summit area. Maximum displacements in the order of tens of centimeters may involve the summit area, up to some 106 m3/m over some kilometers laterally. Stress releases up to 107 Pa may affect a limited portion of the magmatic conduit, thus favoring major effusive flank eruptions. Major catastrophic events, such as volcano flank collapse, should not be expected by applying, either individually or combined, the aforementioned actions.